Pelatihan Penilaian Online untuk Guru Sekolah Dasar: Persepsi dan Hasil Belajar - Ence Surahman; Agus Wedi; Yerry Soepriyanto; Saida Ulfa (Politeknik Piksi Ganesha Indonesia, 2024)
Online assessment has developed massively since the practice of online learning, but its practice in elementary schools has not been widely explored. The study aimed to investigate the perception of satisfaction and its influence in improving the elementary school teachers knowledge from online assessment training. This study involved 37 elementary school teachers from 5 public and private schools in Malang City and was carried out in a pre-test and post-test design. The training was carried out face-to-face and online mentoring for 32 hours. The measuring instrument used triangulation of pre-test post-test data, observation and online questionnaires. Data analysis used descriptive statistics and gain score analysis using Cohen-D. The results showed a positive perception from the training participants who explained that the training could encourage and improve understanding of the urgency of teacher professional development programs. There was a significant increase in understanding based on Cohen-D test data of 1.19. The findings of this study are expected to contribute to strengthening the theory of elementary school teacher professional development programs and encouraging more massive use of technology in the learning assessment process in elementary schools.